2020
DOI: 10.1021/acsaem.0c01590
|View full text |Cite
|
Sign up to set email alerts
|

Design of Three-Dimensional Hollow-Sphere Architecture of Ti3C2Tx MXene with Graphitic Carbon Nitride Nanoshells for Efficient Photocatalytic Hydrogen Evolution

Abstract: Photocatalytic water splitting is the most environmentally friendly method to generate energy. Despite intense research in this area, rapid charge-carrier recombination and limited light absorption of semiconductor-based photocatalysts remain key challenges. Herein, protonated g-C 3 N 4 /Ti 3 C 2 T x MXene hollow spheres, fabricated by electrostatic layer-by layer assembly and a sacrificial template, were used for effective photocatalytic hydrogen (H 2 ) evolution. The constructed three-dimensional (3D) hollow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 63 publications
(88 reference statements)
0
43
0
Order By: Relevance
“…265 Modifications in MXene such as creating 3-D hollow morphological structure and oxygen vacancies (OV) are also done for superior performance. 266,267 For example, Tahir et al not only observed that the creation of oxygen vacant sites in MXene enhances the optical absorption and charge transportation but also found that, due to high electron conductivity, the synthesized material showed promising results for selective CO 2 methanation. 267 Other variations in MXene such as delamination (d-Ti 3 C 2 ) are performed to provide a homogeneous and uniform distribution while making composites with g-C 3 N 4 .…”
Section: Carbon Nitride-mxenesmentioning
confidence: 99%
See 1 more Smart Citation
“…265 Modifications in MXene such as creating 3-D hollow morphological structure and oxygen vacancies (OV) are also done for superior performance. 266,267 For example, Tahir et al not only observed that the creation of oxygen vacant sites in MXene enhances the optical absorption and charge transportation but also found that, due to high electron conductivity, the synthesized material showed promising results for selective CO 2 methanation. 267 Other variations in MXene such as delamination (d-Ti 3 C 2 ) are performed to provide a homogeneous and uniform distribution while making composites with g-C 3 N 4 .…”
Section: Carbon Nitride-mxenesmentioning
confidence: 99%
“…Besides, black phosphorus quantum dots (BQs) with high absorption coefficients, tunable band gap, high hole mobility, and excellent quantum confinement effects have also been employed alongside g-C 3 N 4 nanosheets. , However, MXene is used as an intermediate to fast track transmission of photogenerated charges and also to overcome the shortcomings of BQ/g-C 3 N 4 such as low interfacial contact and low charge carrier mobility . Modifications in MXene such as creating 3-D hollow morphological structure and oxygen vacancies (OV) are also done for superior performance. , For example, Tahir et al not only observed that the creation of oxygen vacant sites in MXene enhances the optical absorption and charge transportation but also found that, due to high electron conductivity, the synthesized material showed promising results for selective CO 2 methanation …”
Section: Carbon Nitride-mxenesmentioning
confidence: 99%
“…Hydrogen energy plays a crucial role in replacing traditional fossil fuels, owing to its high energy density and environmental friendliness . Sustainable hydrogen generated from photocatalytic water splitting has become a current hot topic, and numerous semiconductors have been reported, such as TiO 2 , ZnO, CdS, ZnIn 2 S 4 , carbon nitride, etc . As one of the ternary metal chalcogenides, ZnIn 2 S 4 with a two-dimensional (2D) ultrathin layered structure and a moderate band gap of ∼2.48 eV possesses the advantages of a large surface area, a remarkable visible light response, and unique optical properties . Nevertheless, the photocatalytic hydrogen evolution of ZnIn 2 S 4 is limited by the rapid charge recombination .…”
Section: Introductionmentioning
confidence: 99%
“…78 Accordingly, Kang et al highlighted that the g-C 3 N 4 integrated with Ti 3 C 2 MXene hollow spheres profoundly generated 1.22-fold higher hydrogen than the intrinsic g-C 3 N 4 /Ti 3 C 2 MXene composite. 79 An improved photocatalytic activity was ascribed due to the hollow structure morphology enhancing the specific surface area from 77.4 to 100.1 m 2 g −1 , which aided in the reactant adsorption.…”
Section: Ti 3 C 2 Mxene As a Photoactivity Enhancermentioning
confidence: 99%